MODEL MATEMATIKA PERILAKU MANUSIA SAAT TERJADINYA BENCANA - Hana Fadhila; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — Catastrophe are events that cannot be predicted accurately and have a devastating effect both psychologically and non-psychologically on humans, if there is not enough preparation. Anticipation is a crisis point for the population and operational services in charge during a crisis situation, because it helps ensure the safety of the population and keep the situation under control. This research is related to modelling temporal dynamics of human behaviour during catastrophic event. Several complex models with different scales can be found in order to model crowd dynamics. Thus, in this research included mathematicians, geographers and computer scientist taking into account the human reaction in situation of disaster psychologically and learn their propagation mode. By using SIR based model, which is three types of collective behavior occur during the catastrophe: reflex, panic and controlled. The interaction among these classes of population by emotional contagion and imitation, some simulations will show the relevance of the model. Keywords — Mathematical Model, Human Behavior, Catastrophe, Panic.